Ideological Translations of Robert Burns’s Poetry in Russia and in the Soviet Union - Kaloh Vid, Natalia (2011)
From Marx to Burns to Marshak, Natalia Kaloh Vid takes us on an inspiring and attention-grabbing journey to explain why Robert Burns has and continues to be so popular in Russia. You will discover, as I did, the answer in this much needed book which opens a new frontier for all Burnsians. Samuil Marshak is a name you will come to respect, and for years to come you will be grateful to the author who is one of the new stars on the Burns stage! Not only is this a story worth telling, it is one worth reading.